Economic evaluations of clinical pharmacy services in the United States: 2011‐2017. Issue 4 (27th December 2019) - Talon, Brian; Perez, Alexandra; Yan, Connie; Alobaidi, Ali; Zhang, Katherine H.; Schultz, Bob G.; Suda, Katie J.; Touchette, Daniel R.
Abstract: Studies evaluating the cost‐effectiveness of clinical pharmacy services (CPS) are needed to justify implementation and reimbursement. Through a systematic review, we describe services provided by pharmacists and their economic outcomes. We conducted a literature search of published studies in PubMed, Ovid, and Embase from January 2011 through December 2017. Manuscripts evaluating a CPS with patient‐level economic outcomes and conducted in the United States were included. Study risks of bias were classified by study design characteristics. Economic evaluations were classified according to the presence of a comparator, and cost and outcome measures included. The quality of full economic evaluations was assessed using the Quality of Health Economic Studies (QHES) instrument. Descriptive statistics were used to summarize CPS characteristics. After screening, 115 studies were included. Type of service provided included general pharmacotherapy (41%), disease management (30%), and targeted drug program (17%). Settings included hospital (34%), ambulatory care (28%), and community pharmacy (17%). Study designs were considered high risk of bias (use of a historical control group or no control group) in 69% of cases while 25% were medium risk of bias (non‐randomized with a concurrent control group) and 6% were low risk of bias (randomized experimental or multigroup interrupted time series). Economic evaluation types were descriptive studies that measured cost and/or outcomes of a CPS (55%), comparative studies that measured cost or outcomes of a CPS and a comparator (37%), and full evaluations that measured cost and outcomes of a CPS and a comparator (8%). Among nine full evaluations, the median (range) QHES score was 74 (59‐95) and four reported the CPS as being more effective at a lower cost. Few full economic evaluations were conducted, but supported the cost‐effectiveness of CPS. Use of a comparator group and measurement of economic inputs and outcomes would strengthen the body of evidence.